Crisis and promise in the Caribbean politics and convergence - Dookeran, Winston C. (International political economy of new regionalisms series, 2015)
The Caribbean is made up of a complex, enigmatic region, characterised by great disparities in size, population, geography, history, language, religion, race and politics. This is a region in which harmony and discord work in tandem, trying to link economic logic with political logic. This book is a useful tool not only for those specialists and students of regionalism but for all those putting their hands to the task of nation-building and those interested in the development processes of small states and economies. At the same time, this book is a comprehensive historical record especially highlighting hindrances to development in this region. This study raises two important issues: the 'political imperative of convergence' and the need for 'appropriate correcting mechanisms' that align the needs of the local with the regional. It is a volume that underlines the need for a change in strategy and makes proposals as to how to go about making those changes.